Enhancing quantum control by bootstrapping a quantum processor of 12 qubits. (December 2017) - Lu, Dawei; Li, Keren; Li, Jun; Katiyar, Hemant; Park, Annie; Feng, Guanru; Xin, Tao; Li, Hang; Long, Guilu; Brodutch, Aharon; Baugh, Jonathan; Zeng, Bei; et al.
Abstract Accurate and efficient control of quantum systems is one of the central challenges for quantum information processing. Current state-of-the-art experiments rarely go beyond 10 qubits and in most cases demonstrate only limited control. Here we demonstrate control of a 12-qubit system, and show that the system can be employed as a quantum processor to optimize its own control sequence by using measurement-based feedback control (MQFC). The final product is a control sequence for a complex 12-qubit task: preparation of a 12-coherent state. The control sequence is about 10% more accurate than the one generated by the standard (classical) technique, showing that MQFC can correct for unknown imperfections. Apart from demonstrating a high level of control over a relatively large system, our results show that even at the 12-qubit level, a quantum processor can be a useful lab instrument. As an extension of our work, we propose a method for combining the MQFC technique with a twirling protocol, to optimize the control sequence that produces a desired Clifford gate. Headline: Bootstrapping a 12-qubit quantum processor Realizing high accuracy control of quantum systems represents a crucial ingredient in building large-scaled quantum computers. An international team of researchers led by Raymond Laflamme at Canada's Institute for Quantum Computing has succeeded in manipulating a 12-qubit nuclear magnetic resonance quantum processor with unprecedented precision. The researchers build a closed-loop pulse auto-tunning setup which employs the controlled system itself to optimize its own pulses. This gives to the benefits of more efficient pulse optimization and more robustness to system uncertainties. Because that the experiment achieves high level of individual controls over all of the qubits, it is at the cutting edge of experimental quantum computing. The experimental techniques are ready to be transferred to other quantum technologies, such as nitrogen-vacancy centers, trapped ions or superconducting circuits.